Association of selenium and copper with lipids in umbilical cord blood - Wells, E. M. (2014)
Altered levels of selenium and copper have been linked with altered cardiovascular disease risk factors including changes in blood triglyceride and cholesterol levels. However, it is unclear whether this can be observed prenatally. This cross-sectional study includes 274 singleton births from 2004 to 2005 in Baltimore, Maryland. We measured umbilical cord serum selenium and copper using inductively coupled plasma mass spectrometry. We evaluated exposure levels vis-à-vis umbilical cord serum triglyceride and total cholesterol concentrations in multivariable regression models adjusted for gestational age, birth weight, maternal age, race, parity, smoking, prepregnancy body mass index, n-3 fatty acids and methyl mercury. The percent difference in triglycerides comparing those in the highest v. lowest quartile of selenium was 22.3% (95% confidence interval (CI): 7.1, 39.7). For copper this was 43.8% (95% CI: 25.9, 64.3). In multivariable models including both copper and selenium as covariates, copper, but not selenium, maintained a statistically significant association with increased triglycerides (percent difference: 40.7%, 95% CI: 22.1, 62.1). There was limited evidence of a relationship of increasing selenium with increasing total cholesterol. Our findings provide evidence that higher serum copper levels are associated with higher serum triglycerides in newborns, but should be confirmed in larger studies.